1985
DOI: 10.1002/art.1780280409
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage nucleoside triphosphate pyrophosphohydrolase. II. role in extracellular pyrophosphate generation and nucleotide metabolism

Abstract: Extracellular generation of inorganic pyrophosphate (PPi) in cartilage organ culture is markedly augmented by ATP. ATP, not an ATP metabolite (ADP, AMP, adenosine), is necessary for this augmentation. Excess PPi production is effectively blocked by known inhibitors of nucleoside triphosphate (NTP) pyrophosphohydrolase (EDTA, EGTA, dithiothreitol). Excess 32P-PPi is generated directly from g2P-ATP by cartilage, as substrate and product have similar specific activities. These findings strongly favor ecto-NTP pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This study therefore accords with previous reports in showing (a) higher synovial fluid PPi concentrations and NTPase activities in pyrophosphate arthropathy than in osteoarthritis and (b) lower values in rheumatoid arthritis than in pyrophosphate arthropathy or osteoarthritis. For example, Rachow et al,35 using the radiometric method of Cheung and Suhadolnik,'9 found significant differences in PPi concentrations in synovial fluid from various joints (knees, shoulders, hips) of 40 patients with osteoarthritis and 27 with pyrophosphate arthropathy (mean (SD) 14 (5) and 18 (8) [imol/I respectively); correspondingly higher NTPase activity was found in pyrophosphate arthropathy. Silcox and McCarty, using a differential colorimetric method, measured synovial fluid PPi in 35 patients with osteoarthritis, 29 with pyrophosphate arthropathy, and 12 with rheumatoid arthritis and found mean (range) concentrations of 9-2 (3-35), (4-24), and 4-2 (2-8) [imol/l respectively8; the differences between rheumatoid arthritis and both osteoarthritis and pyrophosphate arthropathy were significant (Student's t test).…”
Section: Resultsmentioning
confidence: 99%
“…This study therefore accords with previous reports in showing (a) higher synovial fluid PPi concentrations and NTPase activities in pyrophosphate arthropathy than in osteoarthritis and (b) lower values in rheumatoid arthritis than in pyrophosphate arthropathy or osteoarthritis. For example, Rachow et al,35 using the radiometric method of Cheung and Suhadolnik,'9 found significant differences in PPi concentrations in synovial fluid from various joints (knees, shoulders, hips) of 40 patients with osteoarthritis and 27 with pyrophosphate arthropathy (mean (SD) 14 (5) and 18 (8) [imol/I respectively); correspondingly higher NTPase activity was found in pyrophosphate arthropathy. Silcox and McCarty, using a differential colorimetric method, measured synovial fluid PPi in 35 patients with osteoarthritis, 29 with pyrophosphate arthropathy, and 12 with rheumatoid arthritis and found mean (range) concentrations of 9-2 (3-35), (4-24), and 4-2 (2-8) [imol/l respectively8; the differences between rheumatoid arthritis and both osteoarthritis and pyrophosphate arthropathy were significant (Student's t test).…”
Section: Resultsmentioning
confidence: 99%
“…ePPi can be generated from eATP through the action of ecto-enzymes with nucleoside triphosphate pyrophosphohydrolase (NTPPPH) activity, such as ENPP1. Because there is ample ENPP1 activity in normal cartilage to convert all available NTP to NMP and PPi, substrate availability is the rate-limiting step in this reaction [11]. We recently demonstrated that chondrocyte eATP and ePPi elaboration were coordinately regulated [8], supporting a major role for eATP in ePPi production by cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the release of cartilage breakdown products (10,20) and crystals, which include calcium pyrophosphate dihydrate and apatite crystals (21)(22)(23), could play an important role. These particles will eventually be phagocytosed by synovial cells and initia.te an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%